281 Burn related violence against women and girls: An ISBI Initiative. (20th November 2022) - Singer, Yvonne; Peck, Mike; Malic, Claudia
Abstract : Introduction: Violence against women and girls (VAW) is a global public health problem. Burn-related violence against women and girls (BVAW) has been reported in many countries regardless of national income. The international burns community has unique insights into BVAW and play a major role in BVAW secondary prevention. In 2018, the International Society of Burn Injuries (ISBI) Prevention Committee's (ISBIPC) began the 'Burn-related violence against women and girls initiative'. Methods: A BVAW integrative review was published by ISBIPC members and colleagues in 2021. In 2022, ISBIPC members and Australian colleagues have begun an Australian BVAW research study involving analysis of BVAW data within the Burn Registry of Australia and New Zealand (BRANZ). BRANZ collects data on people with burn injuries admitted to Australian and New Zealand burn centres for 24 hours or more. A BVAW secondary prevention project is occurring concurrently involving: benchmarking current BVAW identification and intervention practices in Australian burn centres, a literature review to summarise evidence regarding the efficacy of BVAW secondary prevention programs, engagement with national family/interpersonal violence stakeholders to develop standardised Australian burn centre guidelines for BVAW identification and intervention. Results: Kornhaber et al's integrative review, which included 15 studies, identified that the social determinants of health risk factors for BVAW were similar to risk factors for broader VAW. These included low socioeconomic status, unemployment, illiteracy, lack of financial independence, and living in cultures more tolerant of gender inequality. Perpetrators of BVAW were mostly spouses of injured women in context of marital, family or financial issues. Injuries were mostly caused by flames or acid, and were associated with high mortality. Overall limited BVAW evidence exists. Results from the registry study and advocacy plan will be presented at the congress. Learning Outcomes: BVAW like VAW is socially complex and multicausal. The burns community has an opportunity and responsibility to optimise interventions in burn centres for BVAW secondary prevention. Effective sustainable solutions require collaboration across organisational and professional boundaries. Following the initial Australian trial, the ISBIPC plans to replicate the BVAW secondary prevention project in other countries.